Determinants and patterns of treating Hemorrhoid (JediJedi) in Ekiti state, Nigeria - A. O. Arogundade; Kayode Emmanuel Igbekoyi; O. A. Ijabadeniyi (Traditional Medicine and Modern Medicine)
Background to the study: Hemorrhoid is a common and unavoidable situation that cuts across all categories, irrespective of class, status, gender, educational attainment, spiritual or religious beliefs, and affiliations. Hemorrhoid is a benign anorectal disease which has affected millions of people across the globe. Aim and objectives: The study investigates the determinants and patterns of treating hemorrhoids (Jedijedi) in Ekiti State, Nigeria. Materials and methods: The study is a survey research study in which a quantitative method was adopted. Multistage sampling was adopted in selecting 492 respondents from the general populace in Ekiti State. A questionnaire was used to collect data and it was analyzed and presented in frequency percentage. Results: Religious beliefs do not determine patients’ choice of medication (49.0%), peer group determines the impact on patients’ choice of medication for Jedijedi treatment (53.3%), 53.0% affirmed that age determines the choice of treating Jedijedi, about 49% attested that gender determines their choice of treatment, and 41.6% confirmed that income determines their choice of hemorrhoid medication. Conclusion: The study concluded that treatment pattern constructs have effects on the treatment of hemorrhoids (Jedijedi). Recommendations: Government and relevant stakeholders should sensitize the public, and also encourage a wide lab test for local herbs.